Exposure to radiofrequency electromagnetic fields and IARC carcinogen assessment: Risk of Bias preliminary literature assessment for 10 key characteristics of human carcinogens - Myrtill Simkó; Michael H. Repacholi; Kenneth R. Foster; Mats-Olof Mattsson; Rodney J. Croft; Maria Rosaria Scarfi; Vijayalaxmi (Mutation Research - Reviews in Mutation Research, 2025)

Acute effects of Δ9-tetrahydrocannabinol and cannabidiol on auditory mismatch negativity - Lisa-Marie Greenwood; Samantha J. Broyd; Hendrika H. van Hell; Juanita Todd; Alison Jones; Robin M. Murray; Rodney J. Croft; Patricia T. Michie; Nadia Solowij (Psychopharmacology, 2022)

Wi-fi related radiofrequency electromagnetic fields (RF-EMF): a pilot experimental study of personal exposure and risk perception - Berihun M. Zeleke; Christopher Brzozek; Chhavi R. Bhatt; Michael J. Abramson; Frederik Freudenstein; Rodney J. Croft; Peter Wiedemann; Geza Benke (Journal of Environmental Health Science and Engineering, 2021)
The impact of providing people with an objectively measured personal radiofrequency electromagnetic fields (RF-EMF) exposure information on the risk perception of people is not well understood. We conducted an experimental study, among three groups of participants, to investigate the risk perception of people towards RF-EMF from Wi-Fi sources (ISM 2.4 GHz) by providing participants with either basic text, precautionary information, or a summary of their personal RF-EMF exposure measurement levels. Participants provided with personal RF-EMF exposure measurement information were more confident in protecting themselves from RF-EMF exposure, compared to those provided with only basic information. Nonetheless, neither the exposure perception nor the risk perception of people to Wi-Fi related RF-EMF differed by the type of information provided. The measured Wi-Fi signal levels were far below international exposure limits. Furthermore, self-rated levels of personal RF-EMF exposure perception were not associated with objectively measured RF-EMF exposure levels. Providing people with objectively measured information may help them build confidence in protecting themselves from Wi-Fi related RF-EMF exposure.

Hyperthermia, but not dehydration, alters the electrical activity of the brain - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Nigel A. S. Taylor; Rodney J. Croft (European Journal of Applied Physiology, 2020)

Hyperthermia and dehydration: their independent and combined influences on physiological function during rest and exercise - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Rodney J. Croft; Gregory E. Peoples; Nigel A. S. Taylor (European Journal of Applied Physiology, 2020)

The independent influences of heat strain and dehydration upon cognition - Anne M. J. van den Heuvel; Benjamin J. Haberley; David J. R. Hoyle; Nigel A. S. Taylor; Rodney J. Croft (European Journal of Applied Physiology, 2017)

The effect of d,l-methamphetamine on simulated driving performance - Beata Y. Silber; Rodney J. Croft; Luke A. Downey; David A. Camfield; Katherine Papafotiou; Phillip Swann; Con Stough (Psychopharmacology, 2012)

The effect of sleep deprivation on BOLD activity elicited by a divided attention task - Melinda L. Jackson; Matthew E. Hughes; Rodney J. Croft; Mark E. Howard; David Crewther; Gerard A. Kennedy; Katherine Owens; Rob J. Pierce; Fergal J. O’Donoghue; Patrick Johnston (Brain Imaging and Behavior, 2011)

ERP correlates of response inhibition after-effects in the stop signal task - Daniel J. Upton; Peter G. Enticott; Rodney J. Croft; Nicholas R. Cooper; Paul B. Fitzgerald (Experimental Brain Research, 2010)

Acute dopamine and/or serotonin depletion does not modulate mismatch negativity (MMN) in healthy human participants - Sumie Leung; Rodney J. Croft; Valérie Guille; Kirsty Scholes; Barry V. O’Neill; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2010)

Evidence for modulation of facial emotional processing bias during emotional expression decoding by serotonergic and noradrenergic antidepressants: an event-related potential (ERP) study - Rebecca Kerestes; Izelle Labuschagne; Rodney J. Croft; Barry V. O’Neill; Zubin Bhagwagar; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2009)

Acute high-dose glycine attenuates mismatch negativity (MMN) in healthy human controls - Sumie Leung; Rodney J. Croft; Barry V. O’Neill; Pradeep J. Nathan (Psychopharmacology, 2008)

High-dose glycine inhibits the loudness dependence of the auditory evoked potential (LDAEP) in healthy humans - Barry V. O’Neill; Rodney J. Croft; Sumie Leung; Chris Oliver; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2007)

Acute dopamine D1 and D2 receptor stimulation does not modulate mismatch negativity (MMN) in healthy human subjects - Sumie Leung; Rodney J. Croft; Torsten Baldeweg; Pradeep J. Nathan (Psychopharmacology, 2007)

Dopamine receptor stimulation does not modulate the loudness dependence of the auditory evoked potential in humans - Barry V. O’Neill; Rodney J. Croft; Sumie Leung; Valérie Guille; Matthew Galloway; K. Luan Phan; Pradeep J. Nathan (Psychopharmacology, 2006)

The acute effects of d-amphetamine and methamphetamine on attention and psychomotor performance - Beata Y. Silber; Rodney J. Croft; Katherine Papafotiou; Con Stough (Psychopharmacology, 2006)

An evaluation of the sensitivity of the standardised field sobriety tests to detect the presence of amphetamine - Beata Y. Silber; Katherine Papafotiou; Rodney J. Croft; Con K. K. Stough (Psychopharmacology, 2005)

The relative contributions of ecstasy and cannabis to cognitive impairment - Rodney J. Croft; Alex J. Mackay; Alex T.D. Mills; John G.H. Gruzelier (Psychopharmacology, 2001)